Mountain witches : Yamauba - Reider, Noriko T. (Utah State University Press, an imprint of University Press of Colorado, 2021)
"A guide to the complex figure of Yamauba-female yōkai often translated as mountain witches, who are commonly described as tall, enigmatic women with long hair, piercing eyes, and living in the mountains-evolution of their roles and significance in Japanese culture from the premodern era to present" --